1994
DOI: 10.1093/rheumatology/33.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Concentration in Non-Inflamed and Rheumatoid Synovium

Abstract: The concentration of hyaluronan was measured by a novel application of an ELISA technique, using biotinylated hyaluronan binding-region (HABr) derived from cartilage proteoglycan core-protein, to digested frozen sections of synovium. The relative extractability of hyaluronan, from sections of synovium by short-term washes in buffer, was assessed by the same method. The distribution of hyaluronan in adjacent sections was assessed histochemically using the biotinylated HABr and alkaline phosphatase-conjugated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…HA Assay-An enzyme-linked immunosorbance-based assay was used to measure concentrations of HA released into the culture media 24 h after mechanical strain application (31). The assay is based upon the competition between HA absorbed on to the plate and HA free in solution for binding to biotinylated cartilage proteoglycan binding region (G1 domain) (32).…”
Section: Methodsmentioning
confidence: 99%
“…HA Assay-An enzyme-linked immunosorbance-based assay was used to measure concentrations of HA released into the culture media 24 h after mechanical strain application (31). The assay is based upon the competition between HA absorbed on to the plate and HA free in solution for binding to biotinylated cartilage proteoglycan binding region (G1 domain) (32).…”
Section: Methodsmentioning
confidence: 99%
“…In the inflamed synovium HYA is distributed all through the synovial layers but especially around the vessels [24]. In one study [25] the amount of HYA was measured chemically and it was found that the normal synovium contains 1.07 Ϯ 0.16 mg HYA cm Ϫ3 whilst the rheumatoid synovium seen in RA-patients contains 0.71 Ϯ 0.10 mg HYA cm Ϫ3 . Thus the changes in HYA concentration in the synovial fluid are mirrored in the synovial membrane.…”
Section: Turnover Of Hyaluronan In Joint Diseasementioning
confidence: 99%
“…CD44 has been shown to participate in the migration of leukocytes to inflammatory sites (9 -12), where there is often an increase in CD44ϩ cells due to both the immigration of CD44ϩ leukocytes and to a greater degree of CD44 expression on resident cells (1). CD44 expression is increased on many cell types in inflamed arthritic joints (11,13), in which the synthesis and degradation of HA are also enhanced (14,15).…”
mentioning
confidence: 99%